Process-Oriented Business Modeling - An Application in the Printing Industry - Malsbender, Andrea; Ortbach, Kevin; Plattfaut, Ralf; Voigt, Matthias; Niehaves, Björn (International IFIP Working Conference on Enterprise Interoperability, 2013)
This chapter introduces the process‐oriented business model framework (Octoproz) and its application in an innovation workshop in a real life scenario of a printing industry case company. It reports on the merits and drawbacks of Octoproz for creating business models. The chapter also introduces related work on business modeling and briefly presents the case setting and the methodology. The application of process‐oriented led to well‐structured and mainly comparable business models. The conducted case study at the printing industry led to the manifestation of prior theoretical assumptions and serves as evaluation of the developed Octoproz. The presented Octoproz has a high benefit for practice as business ideas can be structured in a meaningful and comprehensive way. The chapter concludes that the process‐oriented framework is detailed enough to take decisions on profitability and feasibility of a business idea.